The Role of Yorùbá Language Education in Bridging the Gap in Moral Restructuring for National Development - Emoruwa, Oluwatoyin Titilayo (Journal of Advanced Research in Education, 2025)
Indigenous Languages refer to the native languages that belong to a particular place. This research paper is an investigation into the role of Yorùbá language education in providing solutions to the moral vices affecting national development in Nigeria. There have been concerns in the past years over the decrease in values such as hard work, honesty, respect for the elders, communal responsibility, and integrity — all of these and more were a major part of our indigenous cultures. Drawing on sociolinguistic and cultural descriptive analysis, the paper is of the opinion that language is not only a means of communication but also a tangible tool for onward transmission of culture, preservation of positive values (ìwà ọmọlúàbí), and ethical re-orientation. Content analysis of proverbs, folktales, songs, riddles and traditional pedagogies in Yorùbá was employed for the study and the study reveals that Yorùbá language education is an ambodiment of rich moral values that aligns with developmental goals of the nation. It concludes that to bridge the moralvices hindering national unity and development, stakeholders must elevate Yorùbá language education beyond symbolic recognition to a functional medium of instruction and subject of study across all levels and character formation, mose especially at the foundational level of education. Recommendations include implementation of the Nigerian language policy, curriculum reforms, teacher training and re-training, and policy commitment to indigenous language revitalization as part of a broader national development strategy.